PENGARUH TINGKAT KEJENUHAN TERHADAP KINERJA PERAWAT WANITA DI RUANG RAWAT INAP RUMAH SAKIT UMUM ROYAL PRIMA TAHUN 2018 - Dzul Akbar Insani; Sri Lestari Ramadhani Nasution; Suci Erawati; Rapael Ginting (Program Studi Kesehatan Masyarakat Universitas Sari Mutiara Indonesia, 2018)
One of the factors that influence the success rate of hospitals is the performance of nurses. Efforts to improve nurse performance, on the other hand, are to pay attention to nurse work stress. The purpose of this study was to determine the factors that cause stress on the performance of female nurses in the inpatient room. The type of research used is cross-sectional survey research using the explanatory research method. The population is 41 nurses and the entire nurse is used as the respondent (total sampling). Data were analyzed using Chi-square test and logistic regression to obtain OR (Odds Ratio). The results showed the relationship between communication and performance (p = 0.012) and OR value was 6.708 which means that communication with good communication will improve performance by 6.7 times. Saturation of performance (p = 0.006) and OR value is 6.667 means that nurses with a degree of saturation that are overcome well will improve performance by 6.6 times. Award for performance (p = 0.006) and OR value is 6.667 meaning that nurses with good recognition and recognition will improve performance by 6.6 times. Income to performance (p = 0.004) and OR value is 8.762 means that nurses with good income will increase performance by 8.7 times. However, there is no relationship between performance and performance (p = 0.091) and the OR value is 3.102 and the family for performance (p = 0.380) and OR value is 2,000. It is expected that the hospital will pay more attention to the needs and comfort of nurses in carrying out daily tasks in the hospital.